Demand for Farm Insurance Under Financial Constraints. Issue 4 (4th July 2017) - Baráth, Lajos; Bokusheva, Raushan; Fertő, Imre
Abstract : This article investigates the effect of the use of crop insurance on farms' economic performance. The authors hypothesize the existence of reciprocal causation between crop insurance use and the economic performance of farms in an environment characterized by imperfect financial markets and farm budget constraints. The results confirm the reciprocal causation hypothesis. Economic performance is found to positively influence farms' demand for insurance, confirming the significance of budget constraints. Moreover, insurance is found to have a negative effect on Hungarian farms' economic performance, implying that the crop insurance system is inefficient.